Think Piece: Naked Science - Avoiding Methodolatry in an Environmental Education Context - Leigh Price (Environmental Association of Southern Africa, 2013)
Research methodology is significantly political and in this think piece I try to better understand the effect of this politicisation in the production of science. The main focus of the think piece is to identify the dominant methodological discourses and analyse them using techniques borrowed from post-structuralism. From this analysis, I suggest that methodological discourses are reproduced and normalised in much the same way as discourses of, for example, sexuality, and I give examples of this from my experience as a PhD student of environmental education. I also suggest that some transgressive methodologies, such as those associated with postmodernism or participatory research, despite purporting to empower, at times also disempower. Furthermore, all of the methodologies that I analyse are, in one way or another, 'loaded'; they cloak their agendas. From this analysis, I move towards suggesting an alternative critical realist methodology for environmental education which is naked; its agendas are clearly stated, not least because this epistemology does not lend itself to deception. An important part of this critical realist conception of methodology is the idea of 'meta-reflexivity' in which truth is not vulgarly pragmatic or fideistic.